Comprehensive phenotypic characterization of Pseudomonas aeruginosa isolates from cystic fibrosis patients: antimicrobial susceptibility, tolerance, hypermutation, biofilm formation, and antibiofilm activity - Gürpınar Tosun, Öznur; Kart, Didem; Özsezen, Beste; Yalçın, Elmas Ebru; Emiralioğlu, Nagehan; Doğru Ersöz, Deniz; Özçelik, Uğur; Köseoğlu Eser, Özgen (The Turkish Journal of Pediatrics, 2026)
Background. Pseudomonas aeruginosa is an opportunistic pathogen that plays a critical role in chronic lung infections in patients with cystic fibrosis (CF), primarily due to its ability to form biofilms and develop antibiotic resistance. This study aimed to evaluate the biofilm-forming ability and antibiotic resistance profiles of P. aeruginosa isolates obtained from patients with CF, and to investigate the relationship between biofilm production and antimicrobial resistance. Methods. 151 P. aeruginosa isolates were collected from patients with CF attending a university hospital. Antibiotic susceptibility testing was performed using both broth microdilution and gradient diffusion methods. Phenotypic determination of virulence factors was performed using standard plate assays. Biofilm production was quantified using the crystal violet microtiter plate assay and Minimum Biofilm Eradication Concentration (MBEC) assay. Statistical analysis was performed to evaluate the association between biofilm formation and antibiotic resistance. Results. The median age of patients with CF was 11.5 years, with 51.7% being female. Although resistance to certain antibiotics was observed, overall resistance rates remained relatively low, with the highest rate being 11%. A total of 30 (19.9%) P. aeruginosa isolates, showing intra-zone growth, were positive for antibiotic tolerance, while 10 (6.6%) of the 151 isolates exhibited hypermutator phenotypes based on the phenotypic hypermutation test. Biofilm evaluation showed that 14% of isolates were strong biofilm producers, 35.8% moderate, and 21.9% weak. 75 P. aeruginosa isolates were assessed for antibiofilm activity using the MBEC assay. Diallyl disulfide alone showed no significant effect. Combined with ciprofloxacin, it reduced minimum biofilm inhibitory concentration (MBIC) in 16% of isolates, while 28% showed increased MBIC, suggesting antagonism. With tobramycin, 22.3% of isolates showed enhanced antibiofilm activity, indicated by a decrease in MBIC. Conclusion. In our study, while a high level of biofilm production was observed among P. aeruginosa isolates from patients with CF, antibiotic resistance rates were found to be low. These results highlight the need for therapeutic strategies targeting biofilms to improve treatment outcomes in CF-related P. aeruginosa infections. Additionally, our data indicate that low ceftazidime resistance in this cohort supports the use of beta-lactam–based empirical strategies and carbapenem-sparing approaches, while recognizing that these findings may not be directly generalizable beyond the local context.